2020
DOI: 10.3390/ijerph17114029
|View full text |Cite
|
Sign up to set email alerts
|

Algicidal Efficiency and Genotoxic Effects of Phanerochaete chrysosporium against Microcystis aeruginosa

Abstract: Eutrophication has become a severe environmental problem. This study evaluated the algicidal efficiency and genotoxic effects of Microcystis aeruginosa co-cultured with Phanerochaete chrysosporium for 48 h under the optimum conditions of 250 mg/L of P. chrysosporium at 25 °C with dissolved oxygen content of 7.0 mg/L. The results showed that the activity of algal dehydrogenase, superoxide dismutase, and peroxidase were all decreased and the malondialdehyde content increased after co-culturing. Fourier transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…AF-1 (cell-free filtrate) was lower than that of the control at the first 48 h but much higher at 72 h, indicating that some evasive mechanisms were taken to prevent the ROS accumulation in cyanobacterial cells at the initial stage [51]. Similar variations of ROS have been observed in M. aeruginosa KW after being treated with Paucibacter aquatile DH15, and the malondialdehyde (MDA) content and SOD activity related to remove ROS also increased at first and then decreased [61]; The MDA content, CAT and POD activity of M. aeruginosa FACHB-905 also increased quickly when fermentation liquid (5%, v/v) of P. aeruginosa [18] and P. chrysosporium was added quickly [101]; moreover, the responses of M. aeruginosa FACHB-905 cells to Streptomyces sp. KY-34 and Streptomyces sp.…”
Section: Effects Of Anticyanobacterial Microorganisms On Antioxidant ...mentioning
confidence: 62%
See 2 more Smart Citations
“…AF-1 (cell-free filtrate) was lower than that of the control at the first 48 h but much higher at 72 h, indicating that some evasive mechanisms were taken to prevent the ROS accumulation in cyanobacterial cells at the initial stage [51]. Similar variations of ROS have been observed in M. aeruginosa KW after being treated with Paucibacter aquatile DH15, and the malondialdehyde (MDA) content and SOD activity related to remove ROS also increased at first and then decreased [61]; The MDA content, CAT and POD activity of M. aeruginosa FACHB-905 also increased quickly when fermentation liquid (5%, v/v) of P. aeruginosa [18] and P. chrysosporium was added quickly [101]; moreover, the responses of M. aeruginosa FACHB-905 cells to Streptomyces sp. KY-34 and Streptomyces sp.…”
Section: Effects Of Anticyanobacterial Microorganisms On Antioxidant ...mentioning
confidence: 62%
“…It has been reported that the fungus Trichaptum abietinum 1302BG can eliminate four cyanobacteria directly including M. aeruginosa FACH-918 and M. aeruginosa PCC 7806 in 48 h [106]. Some other fungi such as Trichoderma citrinoviride [6], Penicillium chrysogenum [97], Aureobasidium pullulans KKUY070 [98], Lopharia spadicea [99], Phanerochaete chrysosporium [100,101], Irpex lacteus T2b [102], Trametes versicolor F21a [107] and Bjerkandera adusta T1 [103] also show good inhibitory activities against M. aeruginosa. It has been stated that T. citrinoviride and A. pullulans have highly specific anticyanobacterial effects towards Microcystis spp.…”
Section: Anticyanobacterial Fungimentioning
confidence: 99%
See 1 more Smart Citation
“…The control and mitigation measures of Microcystis bloom have been developed and highlighted by researchers. Many algicidal bacteria have been isolated [5,6] and constitute the major group of microorganisms showing inhibitory effects on cyanobacteria [7]. Algicidal bacteria, as a biological control method, are expected to be environmentally friendly and feasible for bloom control [8].…”
Section: Introductionmentioning
confidence: 99%